2017
DOI: 10.1002/jhet.2964
|View full text |Cite
|
Sign up to set email alerts
|

DFT Studied Hetero‐Diels–Alder Cycloaddition for the Domino Synthesis of Spiroheterocycles Fused to Benzothiazole and Chromene/Pyrimidine Rings in Aqueous Media

Abstract: Structurally diverse spiroheterocycles; spiro[pyrimido[2,1‐b]benzothiazole‐3,3′‐chromene]‐2′,4′‐dione, spiro[pyrimido[2,1‐b]benzothiazole‐3,5′‐pyrimidine]‐2′,4′,6′‐trione, and spiro[pyrimido[2,1‐b]benz‐thiazole‐3,2′‐cyclohexane]‐1′,3′‐dione have been synthesized by an environmentally benign, efficient, and facile one‐pot pseudo‐four component reaction of 2‐aminobenzothiazoles with aromatic aldehydes and cyclic β‐diketones in aqueous medium. The process involves hetero‐Diels–Alder cycloaddition and provides fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Most of the syntheses of these spiroheterocycles have been carried out using multicomponent reactions using normally non-environmentally friendly reagents. In 2017, a multicomponent process for the preparation of some of these compounds containing 1,3-diketones was developed [95], as shown in Scheme 13b. Thus, the reaction of 1 equivalent of 4-hydroxycoumarin (87) and 2-amino-6-bromo-4-mehtylbenzothiazole (88) with two equivalents of p-anisaldehyde (89) was studied at different conditions.…”
Section: Miscellaneous Methodologiesmentioning
confidence: 99%
“…Most of the syntheses of these spiroheterocycles have been carried out using multicomponent reactions using normally non-environmentally friendly reagents. In 2017, a multicomponent process for the preparation of some of these compounds containing 1,3-diketones was developed [95], as shown in Scheme 13b. Thus, the reaction of 1 equivalent of 4-hydroxycoumarin (87) and 2-amino-6-bromo-4-mehtylbenzothiazole (88) with two equivalents of p-anisaldehyde (89) was studied at different conditions.…”
Section: Miscellaneous Methodologiesmentioning
confidence: 99%
“…A strategy for the design of spiroheterocycles annulated with biologically active fragments was developed on the example of the pseudo-four-component reaction of 2-amino-6-bromo-4-methylbenzothiazole, 4-anisaldehyde and 4-hydroxycoumarine in the presence of sulfamic acid [ 64 ]. The reaction proceeds in 93% yield in 10 min resulting in the target product 42 ( Scheme 34 ).…”
Section: Aminobenzothiazolesmentioning
confidence: 99%
“…The substituent in the imidazole ring is of principal importance for antiviral activity because it was shown that the replacement of the aryl group by a smaller thiophene substituent drastically increases the antiviral action. A strategy for the design of spiroheterocycles annulated with biologically active fragments was developed on the example of the pseudo-four-component reaction of 2amino-6-bromo-4-methylbenzothiazole, 4-anisaldehyde and 4-hydroxycoumarine in the presence of sulfamic acid [64]. The reaction proceeds in 93% yield in 10 min resulting in the target product 42 (Scheme 34).…”
Section: Scheme 33 Three-component Synthesis Of Quinazoline Derivatives Of 2-aminobenzothiazole 41a-fmentioning
confidence: 99%
“…Polycyclic fused-ring heterocycles containing nitrogen and sulfur atom, are of great importance, especially in the pharmaceutical fields, because of their abundance in nature and their diverse biological properties (26)(27)(28). One of these important compounds, the pyrimido benzazole which is synthesized through Biginelli-like reaction (29,30), was extensively studied for their medicinal applications such as antimicrobial, antifungal, antibacterial, antihypertensive, antiviral and anticancer activities (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). They are also potent HIV integrase inhibitors (25,43), LTD 4 receptor antagonists (34), and are also used for the treatment of bronchial asthma and neurodegenerative disease (37,39,44).…”
Section: Introductionmentioning
confidence: 99%